FLORIAN URBAN - Tower and Slab. Histories of global mass housing - Monclús Fraga, Javier (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
FLORIAN URBAN Tower and Slab. Histories of global mass housing Londres: Routledge, 2012, 208 págs. Idioma: inglés